Discourse on the Narrative of Coexistence for Intercultural Education - Choi, Seungeun; Kim, Youngsoon (European Journal of Social Science Education and Research, 2023)
The changes are rapid and multi-faceted golablly; and, the issues and people in the world are interconnected and interrelated. Transformative cultural change engages a process at the crossroads of our social and political, while challenging historical narratives. Intercultural education aims to achieve a developing and sustainable way of living together in multicultural societies through the creation of understanding of, respect for and dialogue between the different cultural groups. Narrative is a characteristic of human consciousness that draws the sequence of experienced events and proposed actions into unified episodes. Moreover, narratives are closely tied to culture and identity and serve as a medium for constructing our understanding of reality. It is the core of intercultural education that the members who participate in society understand the narrative that mutual cultures have. This paper explores the discourse on the narrative of coexistence for intercultural education. The circular interpretation to the process means narratives are tools for conceptualizing and creating change among diverse others in differnet cultures.